Modern objectives of Ukraine energy security under global challenges - Гораль, Л. Т.; Прокопів, М. І. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
Constant change internal and external factors in the development of the national economy actualize study the issue of economic security of the state. Determining the state of its constituent elements in today's environment is important because it allows promptly take action on the organizational and legal support of economic security. In the article was made the historical overview to the trends of energy independence, the essence of energy security as a functional component of economic security are priorities of energy security, and given rapid analysis of economic policy of Ukraine, determined destabilizing factors of the economic and national security, energy security threats were analyzed on the state level.